The cybersecurity workforce and skills. Issue 100 (January 2021) - Furnell, Steven
Abstract: Cyber security is now an essential requirement for modern organisations, but many face a significant constraint in terms of a lack of skilled personnel to support the required roles and responsibilities. Although numerous related qualifications and certifications are available, it is necessary to understand this landscape in order to make an informed decision about which may signify the skills that are relevant to pursue or recruit. This briefing paper examines the nature of the challenge, presenting evidence of the reported skills shortages, and then proceeding to examine the different forms of qualification that are available, and how security practitioners and employers may usefully identify the options that are best suited to their needs.